Solar‐blind AlGaN MSM photodetectors with 24% external quantum efficiency at 0 V. Issue 20 (1st October 2015) - Brendel, M.; Helbling, M.; Knigge, A.; Brunner, F.; Weyers, M.
Abstract : By utilising an asymmetric metallisation scheme to fabricate an AlGaN‐based solar‐blind metal–semiconductor–metal photodetector, a zero‐bias external quantum efficiency (EQE) of 24% for illumination at 240 nm wavelength from the substrate side was obtained. Moreover, an asymmetric bias‐dependence of dark current and EQE is observed. The EQE saturates at about 38% in reverse direction, whereas in forward direction the presence of an internal gain mechanism is indicated.